From world factory to world investor: the new way of China integrating into the world. Issue 2 (4th May 2017) - Wang, Bijun; Li, Xiang
ABSTRACT: This paper argues that outward direct investment (ODI) is replacing international trade as the new way China integrates into the world. Based on two complementary datasets, we document the pattern of Chinese ODI. We argue that the rapid growth of China's ODI is the result of strong economic development, increasing domestic constraints, and supportive government policies. Compared with trade integration, investment integration involves China more deeply in global business. As a new global investor, China's ODI in the future is full of opportunities, risks, and challenges. The Chinese government should improve bureaucracy coordination and participate more in designing and maintaining international rules to protect ODI interests.